Interlaminar fracture of structural fibre/epoxy composites integrating damage sensing and healing. (September 2022) - Benazzo, F.; Rigamonti, D.; Bettini, P.; Sala, G.; Grande, A.M.
Abstract: Technologies to control and reduce delamination damage in fibre reinforced polymer composites involve the use of fibre optic sensors and self-healing polymers, respectively. While the former technology can monitor the evolution of damage by measuring microscopic variations in the material's strain field, the latter can repair delamination damage by recreating broken interfaces. To evaluate the combination of these technologies, a high-performance epoxy vitrimer was used as the matrix phase of a fibre-glass composites incorporating Fibre Bragg Grating (FBG) sensors. Different laminates, manufactured with varying ratios a dynamic crosslinker and epoxy prepolymer, were compared. The analysis involved thermal characterization, mechanical tests to measure interlaminar fracture toughness, and microscope imaging of the cracked and repaired surfaces. Furthermore, FBG sensors to monitor in-situ damage and healing processes of the composites were employed. It was demonstrated that laminates with a larger proportion of dynamic crosslinker exhibit better repair abilities but lower thermal properties. The average and maximum recorded healing efficiency at the first healing cycle, calculated based on the critical fracture toughness, were at 89% and 95% respectively, while it averaged a steady 50% efficiency after several repairing cycles.